Increasing Activity and Science Learning Outcomes Vibrations, Waves and Sound Matter Through STAD Model - Atmoko, Sigit Setyo; Kumala, Dina Erawati; Gatsinzi, Patrick; Usman, Umar Shehu (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: In this research aims to determine increasing activity and science learning outcomes vibrations, waves and sound matter through student teams-achievment divisions (STAD) model.Methodology: This research is Classroom Action Research implemented in three cycles, each cycle consisting of four stages namely planning, observation, observation and reflection. The subject of this research are students of class VIII B of Pabelan 2 Public Middle School consisting of 32 students of 16 male students and 16 female students. Research instruments include observation guide sheet, questions and documentation guidelines.Main Findings: The results of the research show that the student teams achievement divisions (STAD) learning model can increase the activity and learning outcomes of Class VIII B students at State Middle Schools as evidenced by the increase in student learning completeness in Cycle I, 37.5% of students have completed learning, in Cycle II, 81% of students have completed learning and Cycle III 99% of students completed their studies.Novelty/Originality of this study: This research contributes to research with a new foundation in understanding scientific concepts through an innovative approach using the student teams-achievement divisions (STAD) model. The unique findings highlight STAD's significant contribution in stimulating student engagement and increasing achievement of learning outcomes, bringing new nuances to science education research.